2017
DOI: 10.1002/ijc.30752
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from mesenchymal non-small cell lung cancer cells promote chemoresistance

Abstract: Non-small cell lung cancer (NSCLC) is the most common lung cancer type and the most common cause of mortality in lung cancer patients. NSCLC is often associated with resistance to chemotherapeutics and together with rapid metastatic spread, results in limited treatment options and poor patient survival. NSCLCs are heterogeneous, and consist of epithelial and mesenchymal NSCLC cells. Mesenchymal NSCLC cells are thought to be responsible for the chemoresistance phenotype, but if and how this phenotype can be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 23 publications
1
100
0
Order By: Relevance
“…Similar results were discovered in hepatocellular carcinoma (HCC) in which oncogenic RNAs and proteins, like S100 family members and caveolins could be horizontal transferred to neighboring and distant hepatocytes through exosomes, enhancing the migratory and invasive abilities . In lung cancer, exosomes derived from mesenchymal, oncogenically transformed lung cells could transfer mesenchymal phenotypes and even chemoresistance to recipient cells, via the exosomal transfer of a master epithelial‐mesenchymal transition (EMT) transcription factor, ZEB1 mRNA …”
Section: Exosomes In Sequential Processes Of Tumor Metastasissupporting
confidence: 55%
“…Similar results were discovered in hepatocellular carcinoma (HCC) in which oncogenic RNAs and proteins, like S100 family members and caveolins could be horizontal transferred to neighboring and distant hepatocytes through exosomes, enhancing the migratory and invasive abilities . In lung cancer, exosomes derived from mesenchymal, oncogenically transformed lung cells could transfer mesenchymal phenotypes and even chemoresistance to recipient cells, via the exosomal transfer of a master epithelial‐mesenchymal transition (EMT) transcription factor, ZEB1 mRNA …”
Section: Exosomes In Sequential Processes Of Tumor Metastasissupporting
confidence: 55%
“…This transition from an epithelial to mesenchymal stage, termed epithelial‐to‐mesenchymal transition (EMT), has profound impacts on all stages of cancer progression from initiation, growth, and metastasis, to resistance to therapy . Generally, mesenchymal‐like cancer cells are reported to be migratory, less sensitive to chemotherapies, and show low proliferative ability . The characteristics of these mesenchymal‐like cancer cells are thought to be a common cause for metastatic spread .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a loss of E‐cadherin expression can increase breast cancer cell motility and invasiveness. We recently demonstrated that exosomes released by mesenchymal lung cancer cells can confer chemoresistance and mesenchymal traits to recipient epithelial lung cancer cells . However, just how closely the protein content of breast cancer‐derived exosomes reflects the epithelial and mesenchymal state of parent cancer cells remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that nonsmall cell carcinoma cell‐derived exosome contained anaplastic lymphoma kinase (ALK) carrier reduced the therapeutic effect of ALK inhibitors. Lobb et al . demonstrated that mesenchymal nonsmall cell lung cancer (NSCLC) cells changed the chemotherapy tolerance of recipient cells with increased expressed exosomal ZEB1 mRNA (Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%